Box-Behnken design based CO2 co-gasification of horticultural waste and sewage sludge with addition of ash from waste as catalyst - Kan, Xiang (2020)
CO2 co-gasification of horticultural waste (HW) and sewage sludge (SS) with addition of ash from waste as catalyst in a fixed-bed lab-scale gasifier was comprehensively investigated using Box-Behnken experiment design. Influence of three operating parameters, i.e. loaded ash content, operating temperature, and gasifying agent flow rate was studied. Among the three parameters, temperature is the main driving force for enhancement of cold gas efficiency (CGE) and higher heating value (HHV) of the produced syngas. An increase in the gasifying agent flow rate is found to positively impact CGE, but to negatively affect the HHV of the produced syngas and the CO2 reduction ratio. The increase in ash content is observed to have a negative effect at the beginning, followed by a positive effect near the end on both CGE and HHV of the produced syngas at low temperature. Mathematical models of good accuracy, with R2 0.994 and 0.989 for CGE and HHV of the produced syngas respectively, were developed for optimization of the different indices of the co-gasification process by response surface methodology (RSM). Finally, a KIVA-CHEMKIN based CFD model was implemented to study the combustion performance of the produced syngas in an internal combustion engine (ICE). The engine efficiency is observed to be proportional to HHV of the produced syngas, while inversely proportional to its CO2 content, which may cause engine failure when exceeds 74%v/v, in the present study.